Skin Color and Attractiveness Modulate Empathy for Pain: An Event-Related Potential Study - Yang, Di; Li, Xiong; Zhang, Yinya; Li, Zuoshan; Meng, Jing (Frontiers in Psychology, 2022)
Although racial in-group bias in empathy for pain has been reported, empathic responses to others’ pain may be influenced by other characteristics besides race. To explore whether skin color and attractiveness modulate empathy for pain, we recorded 24 participants’ reactions to painful faces from racial in-group members with different skin color (fair, wheatish, or dark) and attractiveness (more or less attractive) using event-related potentials. Results showed that, for more attractive painful faces, dark skin faces were judged as less painful and elicited smaller N2 amplitudes than fair- and wheatish-skinned faces. However, for less attractive faces, there were no significant differences among the three skin colors. Our findings suggest that empathy for pain toward racial in-group members may be influenced by skin color and attractiveness.